Presurgical time and associated factors as predictors of acute perforated appendicitis: a prospective cohort study in a teaching pediatric hospital in Colombia - Paula Castro; Julián Rincón; Cristian Sánchez; Iván Molina; Giancarlo Buitrago (BMC, 2022)
Abstract Background We aim to determine the association between out and in-hospital factors with time, from the beginning of the symptoms to the surgery, in patients with acute appendicitis treated at Fundación Hospital Pediatrico La Misericordia (HOMI) in Colombia. Methods Eleven month prospective cohort study of pediatric patients at HOMI with acute appendicitis diagnosis taken to surgery. Data from the out-of-hospital phase was collected by surveying parents, and the data regarding the in-hospital phase was completed with medical records. We analyzed the association between the time from the beginning of the symptoms to the surgery, and out and in-hospital factors associated with this time using generalized linear models. Results Eight hundred three patients were included in the study. Total pre-surgical time was longer in perforated appendicitis (PA) group (2.65 days, standard deviation (SD) 1.88 vs. 2.04 days, SD 1.45) (p < 0.01). Factors associated with longer total and out-of-hospital presurgical times were age under 4 years old, lower socioeconomic status, father as a caregiver, self-medication, and underestimating disease severity. Conclusions Out-of-hospital timing determines the longer pre-surgical time in complicated appendicitis. Younger age and lower socioeconomic status affect time significantly. We suggest the implementation of strategies in order to lower prehospital time, rates, and costs of complicated appendicitis.